Rancangan Audit 5R Untuk Mengoptimalkan Preventive Maintenance - Fany Apriliani (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Education is a learning process that actively guides students to develop their self-potential and has a noble character. Islamic boarding schools also have an important role and function in education, da'wah, and community empowerment. As national education providers, they need to facilitate dormitories that meet the following aspects: capacity, comfort, cleanliness, health, and security. The problems are: the community often perceives the Islamic boarding school’s environment as poorly maintained, and the students often have various health complaints. This view needs to be proven by direct observation. Good housekeeping activities need to be evaluated regularly. This study aims to design the 5R auditas a guide for evaluating good housekeeping practices to succeedin the preventive maintenance pillar. The study object is one of the Islamic boarding schools in Bogor. The methods are 5R culture training, questionnaires, observation, and designing 5R audits. The results show that students’ understanding of 5R cultural concepts and practices increased by 30,1%. The student’s average value for good housekeeping habits reached 89,5%. However, the 5R audit has not been carried out routinely. The urgency of the 5R audit design consists of 5R activity stages, 5R audit check sheet, 5R kaizen sheet, and 5R competition.